Preparation method and device of salt rock-mudstone interface model sample
Through melting and slow-cooling crystallization, salt rock crystals similar to natural layered salt rock structures were grown on the mudstone surface, solving the problem of inaccurate mechanical and permeability characteristics of the salt rock-mile rock interface model samples in the prior art, and achieving higher material performance matching and stability of experimental results.
Patent Information
- Application Number
- CN202411799025.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The prior art has shortcomings in simulating the mechanical and permeability characteristics of the salt rock-milestone interface. The preparation method of cement-based materials cannot accurately reflect the performance of the actual interface, and the different diagenetic mechanisms lead to inaccurate experimental results.
Through melting and slow-cooling crystals, salt rock crystals similar to natural layered salt rock structures are grown on the mudstone surface. The temperature curve is controlled by molds and high-temperature melting furnaces to ensure that the mechanical and permeability characteristics of the salt rock-mile rock interface are close to the real conditions.
The matching degree of the performance of the model main material is improved, the real diagenetic process is restored, the stability and repeatability of the experimental samples are ensured, and more accurate experimental results are provided.
Smart Images

Figure CN119688430A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of geotechnical engineering technology, and in particular to a method and device for preparing a salt rock-mudstone interface model sample. Background Art
[0002] At present, underground salt caverns are widely used in compressed air energy storage, hydrogen energy storage and crude oil storage as a key energy storage facility. Salt caverns are built in salt rock layers with sodium chloride as the main component, and have excellent sealing and long-term stability. However, most of the salt rocks in China are layered salt rocks deposited in the lacustrine phase. These salt rock layers are interspersed with mudstone layers, resulting in a large number of salt rock-mudstone interfaces in the surrounding rocks of the salt caverns. The tensile and shear strengths of these interfaces are weak, and they are prone to slippage when uncoordinated displacement occurs between the two rocks. In this way, the anchoring effect of the interlayer used to suppress the creep of the surrounding rock will fail, resulting in a reduction in the available volume of the salt cavern, and will also affect the mechanical stability of the salt cavern. In addition, after the interface of the two rocks is damaged or even slipped, cracks will be generated between them. When the interlayer crack network is fully developed, it will become a leakage channel for the stored medium, affecting the energy storage economy of the salt cavern. The leaked energy storage medium may also cause accidents such as groundwater pollution and surface fires.
[0003] Therefore, conducting mechanical and permeability experiments on the salt rock-mudstone interface is critical for evaluating the energy storage reliability of salt caverns. However, due to the poor mechanical properties of the interface, the interface is often damaged by drilling mechanical forces, stress release, etc. during the process of drilling and coring, making it difficult to obtain complete and sufficient interface rock samples. To solve this problem, the most commonly used method in academia is to artificially prepare salt rock-mudstone interface model samples, using cement slurry or cement mortar as alternative materials. After the cement slurry or cement mortar is cast in layers, it is pressed using positive stress to achieve bonding between the interfaces. This method utilizes the plasticity of cement slurry and cement mortar, has the advantages of convenient preparation and homogeneous finished products, and can achieve batch preparation of model samples. However, this method has many defects:
[0004] 1. Differences in material properties: The simulated material formed after cement solidification has significant differences in crystal structure and void distribution from the real salt rock and mudstone. Therefore, the prepared rock model is difficult to simulate the actual mechanical properties and permeability properties of the layered salt rock-interlayered mudstone body and the interface between them.
[0005] 2. Different diagenetic mechanisms: The compression effect in the sample preparation process is significantly different from the natural formation process of the layered rock structure of real salt rock-mudstone. Especially in the sedimentary diagenesis process of layered salt rock, the salt rock on one side of the interface will undergo complex melting, dissolution, and crystallization processes under the action of stress and temperature, making the cementation effect of the interface more complicated and difficult to simulate by simple compression. As a result, the experimental results of the interface model cannot accurately reflect the actual situation.
[0006] From the above analysis, it can be seen that the existing layered rock preparation technology has many shortcomings in simulating the mechanical and permeability properties of the layered salt rock-mudstone interface. The present application provides a method and device for preparing a salt rock-mudstone interface model sample, aiming to solve the defects of the above-mentioned prior art. Summary of the invention
[0007] In order to solve the above problems, the present application provides a method and device for preparing a salt rock-mudstone interface model sample, which grows salt rock crystals similar to the natural layered salt rock structure on the mudstone surface by melting and slow cooling crystallization, ensuring that the mechanical and permeability characteristics of the model sample at the salt rock-mudstone interface are close to the real conditions. The technical solution is as follows:
[0008] The first aspect of the present application provides a method for preparing a salt rock-mudstone interface model sample, comprising the following steps: loading a mudstone layer and a salt powder layer in a mold, wherein the salt powder layer is located on the upper part of the mudstone layer; heating the mold loaded with mudstone and salt powder until the salt powder reaches a molten state; then cooling the mold to allow the molten salt to slowly cool and grow and recrystallize, and by controlling the temperature curve of the slow cooling growth of the molten salt, the crystallization process of the molten salt at the interface position between the mudstone layer and the salt powder layer is controlled to prepare a salt rock-mudstone interface model sample that matches the actual rock structure.
[0009] For example, in the method for preparing the salt rock-mudstone interface model sample provided in one embodiment, when heating the mold loaded with mudstone and salt powder, the heating rate is controlled to be 5-10° C. / min.
[0010] For example, in the preparation method of the salt rock-mudstone interface model sample provided in one embodiment, after the mold loaded with mudstone and salt powder is heated to the melting point of the salt powder, it is kept warm so that the salt powder layer is fully melted and sufficient ion diffusion occurs, and the insulation time is determined according to the amount of salt powder.
[0011] For example, in the method for preparing the salt rock-mudstone interface model sample provided in one embodiment, slow cooling is adopted when cooling the mold, and the temperature is controlled to gradually drop to 600-650°C to adjust the supercooling degree, thereby controlling the crystal growth rate.
[0012] For example, in the method for preparing the salt rock-mudstone interface model sample provided in one embodiment, the mold is cooled slowly, and the temperature is controlled to gradually drop to 638° C. to form a crystal nucleus with a stable crystal phase.
[0013] For example, in the method for preparing the salt rock-mudstone interface model sample provided in one embodiment, after the mold temperature drops below 600° C., the cooling rate is controlled to be 1-3° C. / min to ensure a uniform grain structure.
[0014] For example, in the preparation method of the salt rock-mudstone interface model sample provided in one embodiment, the upper surface of the mudstone layer is a flat surface with a certain roughness to serve as a crystallization bed of molten salt, and the salt powder layer is laid on the upper surface of the mudstone layer and covers the upper surface of the mudstone layer.
[0015] For example, in the method for preparing the salt rock-mudstone interface model sample provided in one embodiment, the salt powder layer is high-purity sodium chloride salt powder, and the particle size of the salt powder is above 200 mesh.
[0016] For example, in the preparation method of the salt rock-mudstone interface model sample provided in one embodiment, quartz sand high temperature resistant granular material is added to the salt powder layer as a seed to improve the nucleation efficiency and cementation strength at the interface between the mudstone layer and the salt powder layer.
[0017] The second aspect of the present application provides a preparation device for a salt rock-mudstone interface model sample, comprising a mold and a high-temperature melting furnace, wherein the mold is used to load a mudstone layer and a salt powder layer, and the salt powder layer is located on the upper part of the mudstone layer; the high-temperature melting furnace is used to heat and cool the mold loaded with the mudstone layer and the salt powder layer, and a temperature sensor is provided in the high-temperature melting furnace to monitor the temperature in the furnace, and a temperature program control system electrically connected to the temperature sensor is provided on the high-temperature melting furnace to adjust the temperature change rate and time, and set the temperature curves of the heating, insulation and cooling stages to ensure the temperature accuracy of the salt powder during the melting and crystallization process.
[0018] The beneficial effects of a method and device for preparing a salt rock-mudstone interface model sample provided in some embodiments of the present application are as follows: compared with the traditional cement pressing sample preparation method, the present application adopts a melting salt rock method, in which salt rock crystals similar to the natural layered salt rock structure are grown on the mudstone surface by melting and slow cooling crystallization, ensuring that the mechanical and permeability characteristics of the model sample at the salt rock-mudstone interface are close to the real conditions, and has the following obvious advantages:
[0019] (1) Improving the matching degree of the main material performance of the model: This application uses real mudstone and sodium chloride salt as raw materials for preparation. The prepared mudstone-salt rock composite structure is closer to natural salt rock and mudstone in terms of the rock body, thereby improving the similarity of the mechanical and seepage properties of the rock model.
[0020] (2) Restoring the real diagenesis process: This application uses the melting method to simulate the deposition and phase transformation mechanism of layered salt rock in nature by adjusting the temperature curve. By adjusting the supercooling and grain density of the crystallization process, the crystal structure of the rock model is matched with the real salt rock. The crystal growth, cementation and other processes at the interface between salt rock and mudstone are reproduced from the crystallographic level, ensuring the similarity of the mechanical, seepage and other properties of the interface of the rock model with the natural interface.
[0021] (3) Ensure the stability and repeatability of experimental samples: Through a controllable melting-crystallization process, a stable and uniform rock model is prepared to provide repeatable and reliable experimental results, providing an experimental basis for conducting long-term stability and airtightness research on salt cavern energy storage systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of this specification or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a schematic diagram of the overall structure of the salt rock-mudstone interface model sample preparation device of the present application;
[0024] Figure 2 This is a schematic diagram of the mold structure of the salt rock-mudstone interface model sample preparation device of the present application. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0026] Unless otherwise defined, the technical terms or scientific terms used in the present disclosure should be understood by people with ordinary skills in the field to which the present disclosure belongs. The "first", "second" and similar words used in the present disclosure do not indicate any order, quantity or importance, but are only used to distinguish different components. "Include" or "comprise" and similar words mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects. "Connect" or "connected" and similar words are not limited to physical or mechanical connections, but can include electrical connections, whether direct or indirect. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.
[0027] In view of the shortcomings of existing layered rock preparation technology in simulating the mechanical and permeability characteristics of layered salt rock-mudstone interface, this application proposes a method and device for preparing a salt rock-mudstone interface model sample, aiming to solve the following key technical problems:
[0028] 1. Inaccurate interface mechanics and permeability characteristics: Traditional preparation methods mostly use cement mortar or cement paste to simulate layered interfaces. Although this method is convenient, the mechanical properties and permeability characteristics of cement materials are significantly different from those of real salt rock and mudstone. As a result, the prepared model cannot truly reflect the mechanical behavior and seepage characteristics of the natural interface, affecting the accuracy of the experimental results.
[0029] 2. The interface bonding mechanism of the model is not restored: The cement-based interface material is formed by a pressing process, but the interface bonding strength formed is relatively weak, and the pressed interface cannot effectively simulate the complex thermal history of real salt rock during the sedimentary diagenesis process and the physical and chemical bonding formed by mineral recrystallization, resulting in unstable mechanical and seepage properties.
[0030] 3. The simulation accuracy and uniformity of the samples are not high: In the existing technology, the pressing effects at different positions may be different during the pressing process of cement samples, resulting in large differences in the repeatability and accuracy of the experimental results of the prepared samples, and it is impossible to provide consistent and reliable experimental data.
[0031] In view of this, the present application provides a method and device for preparing a salt rock-mudstone interface model sample, which grows salt rock crystals similar to the natural layered salt rock structure on the mudstone surface through melting and slow cooling crystallization, ensuring that the mechanical and permeability properties of the model sample at the salt rock-mudstone interface are close to real conditions.
[0032] The salt rock-mudstone interface model sample preparation device of the present application is as follows Figure 1-2As shown, it includes: a mold 3 and a high-temperature melting furnace 1, the mold 3 is used to load a mudstone layer 6 and a salt powder layer 5, and the salt powder layer 5 is located on the upper part of the mudstone layer 6; the high-temperature melting furnace 1 is used to heat and cool the mold 3 loaded with the mudstone layer 6 and the salt powder layer 5, and a temperature sensor 2 is provided in the high-temperature melting furnace 1 for monitoring the temperature in the furnace, and a temperature program control system 4 electrically connected to the temperature sensor 2 is provided on the high-temperature melting furnace 1 to accurately adjust the temperature change rate and time, and set the temperature curves of the heating, insulation and cooling stages to ensure the temperature accuracy of the salt powder during the melting and crystallization process.
[0033] Among them, the high-temperature melting furnace 1 is a high-temperature muffle furnace, which is used to heat the salt powder to its molten state (the temperature reaches above 801°C) and control the subsequent cooling and crystallization process; the mold 3 is used to load mudstone and salt powder, has high-temperature thermal shock resistance, and maintains minimal deformation at high temperatures. At the same time, a special coating is coated on the inner surface of the mold 3 to ensure that the salt rock-mudstone interface model sample can be smoothly demolded after preparation.
[0034] The method for preparing a salt rock-mudstone interface model sample using the salt rock-mudstone interface model sample preparation device of the present application is as follows:
[0035] 1. Material preparation
[0036] Mudstone: Select natural mudstone and cut it into the required size of the sample. It is necessary to confirm that the selected mudstone has strong thermal stability under high temperature conditions to avoid excessive deformation or cracks.
[0037] Salt powder: Use high-purity sodium chloride salt powder to avoid excessive impurities affecting the stability of the crystallization process. The particle size of the salt powder should be controlled above 200 mesh to ensure a fast and uniform melting process. High-temperature resistant granular materials such as quartz sand can also be added to the salt powder as seeds to improve the bonding strength at the interface between the mudstone layer 6 and the salt powder layer 5.
[0038] 2. Material loading
[0039] 2.1 Mudstone preparation and loading: The prepared natural mudstone is placed at the bottom of the mold 3. The surface of the mudstone layer 6 should have a certain degree of roughness while being flat as a whole, so as to provide a good crystallization environment for the molten salt and ensure that the molten salt can be evenly distributed on its surface.
[0040] 2.2 Salt powder filling: Evenly spread the sodium chloride salt powder on the surface of the mudstone layer 6. The thickness of the salt powder layer 5 is determined according to the specifications of the model sample to ensure that the molten salt can cover the surface of the mudstone layer 6 and that the composite sample after preparation can reach the required specifications.
[0041] 3. Sample preparation process
[0042] 3.1 Melting process
[0043] Heating stage: The temperature is gradually raised to above 801°C by the high-temperature melting furnace 1. This process requires precise control of the heating rate to avoid damage to the mudstone layer 6, the mold 3 and the structure of the high-temperature melting furnace 1 caused by temperature fluctuations. The heating rate is generally controlled to be 5-10°C / min.
[0044] Insulation stage: The temperature is maintained above the melting point of sodium chloride salt to allow it to fully melt and allow sufficient ion diffusion to occur. The insulation time is determined by the amount of salt powder, generally 1-2 hours. Since the density of salt powder is lower than that of mudstone, it will always be located on the upper part of the mudstone.
[0045] 3.2 Slow cold growth
[0046] The recrystallization of molten salt requires a certain degree of supercooling, that is, the actual phase change (crystallization) temperature must be lower than the phase change temperature (801°C) in the equilibrium state. This difference is the supercooling. Supercooling is the driving force for the crystallization of molten salt. The size and change process of supercooling will affect the grain density and microstructure of the crystallized salt.
[0047] Slow cooling: During the cooling stage, the temperature gradually drops to 600-650℃ to control the crystal growth rate. By adjusting the supercooling, the sodium chloride salt is gradually crystallized to generate a crystal nucleus density and crystal structure similar to that of natural salt rock.
[0048] Crystallization control: After the temperature drops below 600°C, the crystals gradually grow. During this process, the temperature drop rate is controlled at 1-3°C / min to ensure uniform grain structure and avoid the formation of oversized grains or structural defects.
[0049] The preparation of the salt rock-mudstone interface model sample is completed. The prepared salt rock-mudstone interface model can be used for mechanical experiments (such as uniaxial compression and shear strength tests) and permeability experiments to simulate the geological conditions in the salt cavern energy storage system.
[0050] Among them, the magnitude and change process of supercooling will directly affect the grain density and microstructure of the crystalline salt, so the slow cooling growth stage is the key step of this application.
[0051] In the case of rapid cooling and large undercooling, the faster the crystallization rate, the more crystal centers are formed, and the increase in the nucleation rate (the number of crystal nuclei formed per unit time and unit volume) is faster than the growth rate of the crystal nuclei. In the case of growth around multiple crystal centers, the crystals are not easy to grow, so finer grains and larger grain density can be obtained; on the contrary, the slower the crystallization rate, the fewer the number of crystal centers in the system, the more conducive to the growth of crystals, and the crystals are mostly coarse-grained. Therefore, it is necessary to ensure that the temperature drop rate can make the number of crystal nuclei consistent with the real salt rock, and at the same time ensure that the rough surface of the mudstone is the dominant interface position of the crystal bed, and ensure the crystal density and cementation strength at the interface position.
[0052] It is necessary to ensure that the critical supercooling degree of uniform nucleation of sodium chloride is reached during slow cooling growth, which is about 163°C. That is, the temperature curve of slow cooling growth is designed at the benchmark level of 638°C, so that the formed crystal nucleus has a stable crystalline phase. At the same time, during the slow cooling growth process, it is necessary to ensure that the temperature does not drop too fast or the supercooling is too large, otherwise amorphous salt will be generated, and its strength is far different from that of crystalline salt rock.
[0053] In summary, the method of the present application is used to prepare a salt rock-mudstone interface model sample, and the crystal growth process is affected by adjusting the temperature control curve to simulate the crystal structure of salt rocks in different regions. The temperature curve is optimized through multiple experiments, and the nucleation process is designed and adjusted to simulate the crystal structure and grain density at the interface position that are closer to natural salt rocks.
[0054] The preparation method of the salt rock-mudstone interface model sample of the present application grows salt rock crystals similar to the natural layered salt rock structure on the mudstone surface by melting and slow cooling crystallization, ensuring that the mechanical and permeability properties of the model sample at the salt rock-mudstone interface are close to the actual conditions; by accurately designing the temperature curve, adjusting the crystal nucleus density, crystal volume and crystal structure by controlling the supercooling, the crystal growth process close to the natural salt rock is simulated. The present application simulates the diagenetic mechanism of layered salt rock, specifically the melting and recrystallization process of layered salt rock at the interface under the influence of geothermal conditions. The interface model material prepared based on this principle and its related experiments will provide a more reliable experimental basis for the long-term reliability of the salt cavern energy storage system.
[0055] Although the implementation scheme of the present application has been disclosed as above, it is not limited to the applications listed in the specification and implementation modes, and it can be fully applicable to various fields suitable for the present application. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present application is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a salt rock-mudstone interface model sample, characterized in that: The following steps are involved: A mudstone layer and a salt powder layer are loaded into the mold, wherein the salt powder layer is located on the upper part of the mudstone layer; The mold loaded with mudstone and salt powder is heated until the salt powder reaches a molten state; The mold is then cooled down to allow the molten salt to slowly cool and grow and recrystallize. By controlling the temperature curve of the slow cooling growth of the molten salt and the crystallization process of the molten salt at the interface between the mudstone layer and the salt powder layer, a salt rock-mudstone interface model sample matching the actual rock structure is prepared.
2. The method for preparing the salt rock-mudstone interface model sample according to claim 1, characterized in that: When heating the mold loaded with mudstone and salt powder, the heating rate is controlled to be 5-10°C / min.
3. The method for preparing the salt rock-mudstone interface model sample according to claim 2, characterized in that: After the mold loaded with mudstone and salt powder is heated to the melting point of the salt powder, it is kept warm so that the salt powder layer can be fully melted and sufficient ion diffusion can occur. The holding time is determined according to the amount of salt powder.
4. The method for preparing the salt rock-mudstone interface model sample according to claim 3, characterized in that: When cooling the mold, slow cooling is adopted to control the temperature to gradually drop to 600-650℃ to adjust the supercooling degree and thus control the crystal growth rate.
5. The method for preparing the salt rock-mudstone interface model sample according to claim 4, characterized in that: When cooling the mold, a slow cooling process is adopted, and the temperature is controlled to gradually drop to 638°C to form a crystal nucleus with a stable crystal phase.
6. The method for preparing the salt rock-mudstone interface model sample according to claim 5, characterized in that: When the mold temperature drops below 600°C, the cooling rate is controlled to 1-3°C / min to ensure a uniform grain structure.
7. The method for preparing the salt rock-mudstone interface model sample according to claim 1, characterized in that: The upper surface of the mudstone layer is a flat surface with a certain degree of roughness so as to serve as a crystallization bed of molten salt. The salt powder layer is laid on the upper surface of the mudstone layer and covers the upper surface of the mudstone layer.
8. The method for preparing the salt rock-mudstone interface model sample according to claim 1, characterized in that: The salt powder layer is high-purity sodium chloride salt powder, and the particle size of the salt powder is above 200 meshes.
9. The method for preparing the salt rock-mudstone interface model sample according to claim 1, characterized in that: Quartz sand high temperature resistant granular material is added to the salt powder layer as a seed crystal to improve the nucleation efficiency and cementation strength at the interface between the mudstone layer and the salt powder layer.
10. A device for preparing a salt rock-mudstone interface model sample, characterized in that: include: A mold, used for loading a mudstone layer and a salt powder layer, wherein the salt powder layer is located on the upper part of the mudstone layer; A high-temperature melting furnace is used to heat and cool a mold loaded with a mudstone layer and a salt powder layer. A temperature sensor is provided in the high-temperature melting furnace to monitor the temperature in the furnace. A temperature program control system electrically connected to the temperature sensor is provided on the high-temperature melting furnace to adjust the temperature change rate and time, and set the temperature curves of the heating, insulation and cooling stages to ensure the temperature accuracy of the salt powder during the melting and crystallization process.
Citation Information
Patent Citations
Preparation method of inter-salt shale oil reservoir core model
CN108801722A
Granular salt rock reconsolidation test device and test method under hot water force coupling effect
CN115541383A
Manufacturing method of layered salt rock similar material containing insoluble interlayer
CN116399658A
True triaxial fracturing sample capable of reflecting multi-lithology combined rock mass and bedding characteristics and preparation method of true triaxial fracturing sample
CN117232934A
Methods for modeling permeability in layered rock formations
US20190353574A1